Genetic context-dependent regulation of FlbE enhances morphology modulation and citric acid production in Aspergillus niger - Meiling Chen; Xiaomei Zheng; Peng Du; Xiaomeng Ni; Zhimin Li; Ping Zheng; Jibin Sun (Bioresource Technology, 2026)

Environment disturbances influence bacterial diversity, structure and co-occurrence network in the Digitaria sanguinalis rhizosphere - Yiming Dai; Ye Cui; Qingchen Xiao; Meiling Ping; Yiming Zhang; Shiguang Hu; Hao Chen; Xiaoyu Li; Jin Chen (Physiological and Molecular Plant Pathology, 2025)

GDF11 Regulates M1 and M2 Polarization of BV2 Microglial Cells via p38 MAPK Signaling Pathway - Xiangyu Zhao; Rui Qin; Guopeng Li; Gaorong Lv; Di Zhao; Linghua Kong; Meiling Qi; Ping Li (Molecular Neurobiology, 2025)

Altering wilting time and chopping length to optimize Medicago polymorpha L. fermentation ripening rate and flavour - Ning Mao; Hanyu Zhang; Ermei Du; Meiling Fan; Shihao Liu; Chaosheng Liao; Chao Chen; Hong Sun; Yulong Zheng; Ping Li; Yixiao Xie (Food Bioscience, 2025)

Impact of humidity variations at different distances from the lake surface on rhizosphere microbiota of Trifolium repens L - Jin Chen; Meiling Ping; Xiaowan Geng; Keqing Lin; Boyan Wang; Yuxin Zhai; Yizhen Meng; Xiaoyu Li (Physiological and Molecular Plant Pathology, 2025)

Plio-Pleistocene drainage reorganization in the middle Yellow River of China, revealed by provenance and paleocurrent analysis of fluvial sediments - Menghao Li; Zhenbo Hu; Ping Wang; Baotian Pan; David Bridgland; Qinhong Mo; Xiaohua Li; Zijuan Dong; Meiling Zhong; Renzhe Pan; Ningyi Li (Geomorphology, 2024)

Microbial ecological clusters structured by environments drive maize residue decomposition at the continental scale - Meiling Zhang; Shiyu Wang; Liyu Zhang; Wentao Li; Mengmeng Cao; Shuyu Huang; Xinpeng Xu; Ping He; Wei Zhou; Laurent Philippot; Chao Ai (Science of The Total Environment, 2023)

Dorsal and ventral fronto-amygdala networks underlie risky decision-making in age-related cognitive decline - Ping Ren; Manxiu Ma; Yuchuan Zhuang; Jiayin Huang; Meiling Tan; Donghui Wu; Guozhi Luo (GeroScience, 2023)
Older adults often have difficulty in making decisions under uncertainty, increasing the risk of financial exploitation. However, it is still under investigation about the extent to which cognitive decline influences risky decision-making and the underlying neural correlates. We hypothesized that the individual differences of risk-taking behavior depend on cognitive integrity, in which the dorsal and ventral fronto-amygdala connectivity would play dissociable roles. In the current study, thirty-six young and 51 older adults were tested with the Iowa gambling task combing resting-state and task-related functional magnetic resonance imaging. The results showed significant changes in behaviors and the fronto-amygdala network in older adults relative to young adults. More importantly, age-effect on risk-taking behaviors was remarkably different in cognitively normal and impaired older adults. In resting-state analysis, task performance was positively correlated with the ventral fronto-amygdala connectivity and negatively correlated with the dorsal fronto-amygdala connectivity in cognitively impaired older adults, compared with cognitively normal individuals. Furthermore, task-related analysis confirmed the relationships between dorsal/ventral fronto-amygdala network and risk-taking behaviors depending on cognitive integrity. These findings indicate that the fronto-amygdala network is crucial for understanding altered risky decision-making in aging, suggesting dissociable contributions of the dorsal and ventral pathways in the context of cognitive decline.

Pc4, a putative movement protein of Rice stripe virus, interacts with a type I DnaJ protein and a small Hsp of rice - Lianming Lu; Zhenguo Du; Meiling Qin; Ping Wang; Hanhong Lan; Xiaoqing Niu; Dongsheng Jia; Liyan Xie; Qiying Lin; Lianhui Xie; Zujian Wu (Virus Genes, 2009)